Collision with opponents-but not foul play-dominates injury mechanism in professional men's basketball - Leonard Achenbach; Christian Klein; Patrick Luig; Hendrik Bloch; Dominik Schneider; Kai Fehske (BMC, 2021)
Abstract Background To identify injury patterns and mechanisms in professional men's basketball by means of video match analysis. Methods In Germany, injuries are registered with the statutory accident insurance for professional athletes (VBG) by clubs or club physicians as part of occupational accident reporting. Moderate and severe injuries (absence of > 7 days) sustained during basketball competition in one of four seasons (2014-2017 and 2018-2019) in the first or second national men's league in Germany were prospectively analyzed using a newly developed standardized observation form. Season 2017-2018 was excluded because of missing video material. Results Video analysis included 175 (53%) of 329 moderate and severe match injuries. Contact patterns categorized according to the different body sites yielded eight groups of typical injury patterns: one each for the head, shoulders, and ankles, two for the thighs, and three for the knees. Injuries to the head (92%), ankles (76%), shoulders (70%), knees (47%), and thighs (32%) were mainly caused by direct contact. The injury proportion of foul play was 19%. Most injuries (61%) occurred in the central zone below the basket. More injuries occurred during the second (OR 1.8, p = 0.018) and fourth quarter (OR 1.8, p = 0.022) than during the first and third quarter of the match. Conclusion The eight identified injury patterns differed substantially in their mechanisms. Moderate and severe match injuries to the head, shoulders, knees, and ankles were mainly caused by collision with opponents and teammates. Thus, stricter rule enforcement is unlikely to facilitate safer match play.